PENGARUH PSYCHOLOGICAL CAPITAL TERHADAP KINERJA DAN TURNOVER INTENTION KARYAWAN NGO X DENGAN QUALITY OF WORK LIFE SEBAGAI VARIABEL MEDIASI - Ainul Hadi, Hafiz Rahman (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract:  This research aims to determine and analyze the influence of Psychological Capital, Quality of Work Life, Job Performance and Turnover Intention at NGO X which have a development program in West Sumatera, Lampung and South Sulawesi. This research is exploratory research with quantitative method. Sampling technique with census, so sample size of 54 employee. This research uses SEM-PLS with smartPLS 3 program. The results of this research showed that Psychological Capital have positive and significant effect to Quality of Work Life, Psychological Capital have positive and significant effect to Job Performance, while Psychological Capital has a negative not significant effect on Turnover Intention, Quality of Work Life has a positive not significant effect on Job Performance. Afterwards Quality of Work Life have positive and significant effect to Turnover Intention. In this research, the Quality of Work Life as a mediation apparently doesn’t have a role between Psychological Capital with Job Performance and Turnover Intention. Keywords : Psychological Capital, Quality of Work Life, Job Performance, Turnover Intention